サルコイドーシスとの鑑別が困難であった口腔パラコクシジオイデス症の1例 - 濱田, 良樹; 藤原, 久子; 山田, 浩之; 熊谷, 賢一; 岸, 悠太; 中岡, 一敏 (日本口腔外科学会雑誌, 2015)
We report a case of paracoccidioidomycosis that was difficult to differentiate from sarcoidosis. Paracoccidioidomycosis is a deep fungal infection caused by Paracoccidioides brasiliensis. It causes a granulomatous systemic mycosis and is endemic to rural areas of Latin America. A 57-year-old man visited our clinic because of swelling and slight pain in the lower lip. He had been previously been given a diagnosis of sarcoidosis after a histological examination of the tongue and pulmonary lesions, and had received steroid therapy at the respiratory department of a general hospital. We perform biopsy which specimens were taken from the lower lip and tongue. The initial pathological diagnosis was sarcoidosis, based on the presence of granulomas without caseous necrosis. Several months later, when the pain and swelling of lower lip and tongue had worsened, it was found that the patient had grown up in a rural area in Paraguay and that his relatives had suggested the possibility of fungal disease. This led us to suspect endemic fungal disease and additional pathological examination of the same specimen was performed. Giemsa staining and periodic acid-Schiff staining were negative, but Grocott-Gomori’s methenamine silver staining was positive and showed the characteristic features of paracoccidioidomycosis, associated with a so-called Mickey Mouse ears appearance.